Use of internet of things (IOT) on fish feeding tools with nodemcu - Khairul, Habib; Buaton, Relita; Syahputra, Siswan (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
In everyday life whether in the city or in the countryside, there are lots of fish keepers in both large, medium sized ponds or small ones. Raising fish is an activity people who are very popular from the past until now, because ease of maintenance and care that makes most people want to cultivate fish. Fish kept in considered pond must give time to feed so that the fish requires a regular and continuous feeding schedule. ESP8266 NodeMCU is an integrated chip component that designed for today's connected world. these chips offers a complete, unified Wi-Fi networking solution that can used as an application provider or to sell all functions Wi-Fi networking to other application processors. One of its uses namely as an Automatic Fish Feeder Using ESP8266 Based on the Internet of Things (IOT). By using the components of the tool above as well as some supporting software When the tool runs, the fish feeder can automatically work in accordance with the schedule options that have been previously arranged, and capable displays data to web pages in the form of notifications when feed has been given and when the reservoir is empty or exhausted.